Employment and productivity: disentangling employment structure and qualification effects - Bourlès, Renaud; Cette, Gilbert; Cozarenco, Anastasia (Marseille, 2010)
"This paper studies the effect of changes in the employment rate on labour productivity per hour, taking an empirical approach. By splitting the workforce into three qualification categories, this study allows us to distinguish the effects of changes in the employment rate structure from those of changes in the qualification structure. With the results obtained, we are then able to emphasise the mechanical effect on GDP, for each country in our panel, of a catch-up with the best practice with respect to employment rate structure and qualification level. It appears that the two effects are more or less of the same magnitude. Moreover, this methodology allows us to rank the countries in our panel depending on the gains they could expect from adopting the best practices in each of the two areas."